INTEGRATION OF ISLAM AND SCIENCE IN INTERDISCIPLINARY ISLAMIC STUDIES - Hosaini, Hosaini; Akhyak, Akhyak (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This research is very interesting and important to study according to the rational reasons stated in the background content, that science and Islam are knowledge obtained through different epistemological sources. even though in the Islamic view it is explained that Islam is a religion of salvation that does not separate science into dichotomous boxes. This research aims to construct the concept that science and Islam are sciences that originate from an epistemology originating from the creator, namely Allah SWT. This research uses a literature review (SLR) system which includes accredited national journals and several other international journals which includes several stages as follows: a. identification phase. B. filtering phase c. feasibility stage and d. inclusion and extraction phases. Based on the results of data analysis, the resulting research findings are that the Al-Qur'an provides quite high encouragement to develop sciences based on Allah's revelation and sciences based on reason. The knowledge that comes from Allah's revelation is the Koran, while the knowledge that comes from reason is the result of human thought which is developed systematically and scientifically. Thus, it can be concluded that the ulumul Qur'an perspective between science and Islam has been explained in the Qur'an through kauliyah verses which explain its relationship with the universe. Meanwhile, the second verse is the qauniyah verse which is a verse from Allah apart from discussing the universe